Incentive Pay and Systemic Risk - Albuquerque, Rui; Cabral, Luís; Guedes, José (Review of Financial Studies, 2019)
We show that, in the presence of correlated investment opportunities across firms, risk sharing between firm shareholders and firm managers leads to compensation contracts that include relative performance evaluation. These contracts bias investment choices toward correlated investment opportunities, and thus create systemic risk. Furthermore, we show that leverage amplifies all such effects. In the context of the banking industry, we analyze recent policy recommendations for firm managerial pay and show how shareholders optimally undo the policies’ intended effects. Received October 31, 2017; editorial decision August 21, 2018 by Editor Wei Jiang. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.